(untitled) (Journal of Scientific Research, 2025)
In this paper, a five-dimensional Bianchi type cosmological model that has two interacting ideal fluids that are related to dark energy and dark matter, together with a quadratic EOS with time-dependent parameters γ(t) and Λ(t) is obtained. In this work, the Einstein field equations have been solved. Also found equation of state parameter γ(t) and Λ(t) as t→∞. Our outstanding results shows that the resultant universe depends on the parameter γ(t) and Λ(t) for interacting dark energy. Also studied LR and PR behaviors. We discuss the two cases of LR model for the defined Hubble parameter H(t) = H0eγ(t) and H(t) = (tn /τn) - 1 and then discuss the physical parameters for t→0 & t →± ∞. In PR model we consider Hubble parameter H = H0(t) H1e-γt(n+1) and discuss the density for the dark matter for t→0 & t →± ∞. It is observed that, the universe is expanding faster than usual due to influence of coupling between pair DE and DM.